PEMBERIAN EDUKASI TENTANG POSTUR TUBUH YANG BAIK DALAM MENJAGA KESEHATAN TULANG BELAKANG PADA SISWA SD NEGERI 2 CILILIN - Ika Rahman; Fadjar Muhamad K; Gaudensia Wea; Malida Rahmawati (Insight Power (Kekuatan Wawasan), 2022)
Background: The spine is a part of the body that connects the upper and lower extremities, which has an important role in human movement activities, because it functions as a body enforcer and supports body weight. If not properly maintained, the skeleton or bones can experience changes in shape or postural deviations. Posture deviation is a body posture that is formed as a result of increased muscle tension or muscle shortening, while other muscles are elongated and weak due to body errors in behavior during daily activities (Solberg, 2008 in Pristianto et al., 2019). So that it can cause spinal trauma such as deformities such as kyphosis, lordosis, and scoliosis. Objective: To provide counseling and education about maintaining good posture to maintain spinal health for students at SD Negeri 2 Cililin. Methods: Education and posture assessment with visual observation. Results: The results of the evaluation during this counseling activity the students became more attentive to their body postures such as sitting, standing and how to use the bag properly and correctly.Keywords: Spine, Posture, Students